When Do Morally Motivated Innovators Elicit Inspiration Instead of Irritation? - Bolderdijk, Jan Willem; Brouwer, Claire; Cornelissen, Gert (Frontiers in Psychology, 2018)
Innovators (i.e. consumers who are the first to adopt an innovation) are pivotal for the societal diffusion of sustainable innovations. But when are innovators most influential? Recent work suggests that morally-motivated innovators (i.e., consumers who adopt an innovation out of concern for the welfare of others) can make fellow consumers who have not yet adopted that innovation feel morally inadequate. As a self-defense mechanism, those fellow consumers might dismiss these innovators and their choices. As a result, ironically, morally-motivated innovators might discourage others to adopt sustainable innovations. In an experimental study, we replicate this pattern, but also show that moral innovators can elicit a more positive response as well. Specifically, our results offer initial evidence that morally-motivated innovators may be more inspiring than self-interested innovators, provided that their actions do not directly pose a threat to the moral self-concept of observers. In sum, our research sheds empirical light on the conditions under which innovators are likely to facilitate, rather than slow down the transition to a more sustainable society.